Compact Circular/Linear Polarization Dual-Band Prime-Focus Feed for Space Communication - Rastislav Galuscak; Pavel Hazdra; Milos Mazanek (International Journal of Antennas and Propagation)
We propose a novel, compact, prime-focus antenna feed for space communication. The feed requires full-wave simulator optimization for a given parabolic reflector and is designed to operate simultaneously on two bands, offering LHC/RHC polarizations for the 13 cm band and V/H polarizations for the 70 cm band. With performance results confirmed by measurement, it has been verified in practice that this compact feed is suitable for use in a low-noise Earth-Moon-Earth communication link.